INTEGRASI NILAI QUR’ANI DALAM PEMBELAJARAN PAUD: SCOPING REVIEW TENTANG AKHLAK, MORAL, DAN RELIGIUSITAS - Hartin Kurniawati; Ika Rahayu Satyaninrum (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Early Childhood Education (PAUD) plays a fundamental role in shaping children’s character, morality, and religiosity. In the Indonesian context, the integration of Qur’anic values is particularly significant, as it provides not only moral foundations but also holistic spiritual guidance. This study aims to map and analyze how Qur’anic values are integrated into PAUD learning, focusing on strategies, methods, and challenges in cultivating akhlak, moral, and religiosity in early childhood. A scoping review approach was employed by examining relevant literature indexed in Scopus and other reputable databases. The reviewed studies highlight that Qur’anic values are most effectively transmitted through developmentally appropriate methods, such as habituation, teacher modeling, storytelling, play-based learning, and memorization of short surahs and prayers. Findings also reveal that successful integration depends on the synergy between school and family, as well as the selective use of digital media as supporting tools. However, gaps remain in terms of longitudinal evidence, teacher capacity, and policy frameworks to sustain consistent implementation. The study concludes that Qur’anic value integration in PAUD contributes significantly to early moral and religious development. It calls for curriculum enrichment, teacher professional development, and further empirical research with longitudinal and experimental designs to measure long-term impacts. These insights are expected to inform both theory and practice in strengthening Qur’an-based early childhood education.